A Randomized Clinical Trial of Human Papillomavirus Test-and-Treat as Compared to Cytology-Based Screening for Prevention of Cervical Cancer Among Women With Human Immunodeficiency Virus: AIDS Clinical Trials Group Protocol A5282 . (16th March 2022) - Wilkin, Timothy; Chen, Huichao; Sahasrabuddhe, Vikrant; Matining, Roy; Mngqibisa, Rosie; Chinula, Lameck; Mbilizi, Yamikani; Magure, Tsitsi; Omoz-Oarhe, Ayotunde E; Rassool, Mohammed; Riviere, Cynthia; Bhosale, Rhamesh; et al.
Abstract: Background: Cytology-based cervical cancer screening followed by confirmation and treatment of biopsy-proven high-grade squamous intraepithelial lesions (bHSIL) is difficult to implement in resource-constrained settings. We hypothesized that high-risk human papillomavirus (hrHPV) testing followed by immediate cryotherapy of women with hrHPV (HPV screen-and-treat) may improve outcomes. Methods: Randomized, open-label, phase 2, multinational clinical trial enrolling women with human immunodeficiency virus (HIV) age 18 or older with cervical hrHPV and having no cervical lesions or lesions appropriate for cryotherapy. Women were randomized to immediate cryotherapy (Arm A) or cytology-based screening (Arm B). For Arm A, cervical biopsies were obtained followed by cervical cryotherapy, and in Arm B, women with abnormal cytology underwent colposcopy followed by loop electroexcision procedure (LEEP) if bHSIL was detected. Women were followed through 30 months. The primary outcome was time to bHSIL detected from Month 6 through study completion. Results: In total, 288 women (145 in Arm A, 143 in Arm B) were randomized: median age 35 years, 84% on antiretroviral therapy, median CD4 501 cells/mm 3 . In Arm A, 39 (27%) of women had bHSIL at entry, and in Arm B, 88 (62%) had abnormal cytology, 22 (15%) were diagnosed with bHSIL, 12 (8%) underwent LEEP. In follow-up, 30 (21%) and 31 (22%) developed bHSIL; time to bHSIL was similar between arms ( P =.94). The prevalence of hrHPV at Month 6 was similar between arms (61% and 70%, P =.13). Conclusions: HPV test-and-treat was not associated with improved bHSIL outcomes as compared to cytology-based screening. More effective treatment options are required to improve outcomes from screen-and-treat programs. Clinical Trials Registration: NCT01315363. Abstract : Human papillomavirus test-and-treat did not lead to better outcomes for biopsy-proven cervical high-grade squamous intraepithelial lesions in women with human immunodeficiency virus as compared to a cytology-based strategy.